Lung Matrix Metalloproteinase Activation following Partial Hepatic Ischemia/Reperfusion Injury in Rats. (23rd January 2014) - Palladini, Giuseppina; Ferrigno, Andrea; Rizzo, Vittoria; Tarantola, Eleonora; Bertone, Vittorio; Freitas, Isabel; Perlini, Stefano; Richelmi, Plinio; Vairetti, Mariapia
Abstract : Purpose . Warm hepatic ischemia-reperfusion (I/R) injury can lead to multiorgan dysfunction. The aim of the present study was to investigate whether acute liver I/R does affect the function and/or structure of remote organs such as lung, kidney, and heart via modulation of extracellular matrix remodelling. Methods . Male Sprague-Dawley rats were subjected to 30 min partial hepatic ischemia by clamping the hepatic artery and the portal vein. After a 60 min reperfusion, liver, lung, kidney, and heart biopsies and blood samples were collected. Serum hepatic enzymes, creatinine, urea, Troponin I and TNF-alpha, and tissue matrix metalloproteinases (MMP-2, MMP-9), myeloperoxidase (MPO), malondialdehyde (MDA), and morphology were monitored. Results . Serum levels of hepatic enzymes and TNF-alpha were concomitantly increased during hepatic I/R. An increase in hepatic MMP-2 and MMP-9 activities was substantiated by tissue morphology alterations. Notably, acute hepatic I/R affect the lung inasmuch as MMP-9 activity and MPO levels were increased. No difference in MMPs and MPO was observed in kidney and heart. Conclusions . Although the underlying mechanism needs further investigation, this is the first study in which the MMP activation in a distant organ is reported; this event is probably TNF-alpha-mediated and the lung appears as the first remote organ to be involved in hepatic I/R injury.